The Relationship Between Learning Interest and Intrinsic Motivation of Students at QBS SMP IT Cahaya Insani - Agustanti, Anisa; Kinanthi, Zahro Ferli (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study aims to determine the relationship between learning interest and intrinsic motivation among students at QBS SMP IT Cahaya Insani. The research employs a quantitative approach with a correlational method to analyze the relationship between two variables: learning interest (variable X) and intrinsic motivation (variable Y). Data were collected through a questionnaire using a scaling method, which was designed to measure the intensity or level of agreement of respondents with statements related to intrinsic motivation and learning interest. The questionnaire was distributed to 43 students from classes 9A and 9B, selected using purposive sampling from a total population of 132 students. The selection criteria were based on the assumption that these students, having spent more time in school compared to students in grades 7 and 8, would have a higher level of maturity in terms of learning interest and intrinsic motivation. Data analysis was conducted using IBM SPSS Statistics version 25 to ensure the validity, reliability, and robustness of the model used in this research. The results of the study indicate a positive and significant relationship between intrinsic motivation and students' learning interest. This is evidenced by a Pearson correlation value of 0.528, which is greater than the critical value (0.528 > 0.294), with a significance value of 0.000, which is less than 0.05 (0.000 < 0.05). The effective contribution of intrinsic motivation to learning interest was found to be 27.9%, while the remaining 72.1% was influenced by other variables not included in this study.